Only strategic action? Private governance in the global sportswear industry - Philip Schleifer (Freie Universität Berlin, Center for International Political Economy, 2010)
What motivates companies to invest in corporate social responsibility (CSR)? Analysing CSR in the global sportswear industry, this paper advances the hypothesis that the campaigning activities of human rights activists pushed industry leaders Nike and adidas to incorporate labour norms in their business (sourcing) practices. Drawing on the spiral model of human rights norm internalization, the paper's findings suggest that the efforts of leading sportswear companies to address poor labour standards in their supply chains can no longer be explained by mere strategic behaviour induced by external pressure, but are increasingly the result of norm guided behaviour. In the case of adidas and to a lesser extent with regard to Nike evidence points to a prescriptive status in which the dominant mode of action shifts from the logic of consequences to the logic of appropriateness.
urn:nbn:de:101:1-20100422176
Keywords: 330; private governance; private actors; transnational companies; norms; CSR; labour standards; Corporate Social Responsibility; Sozialstandards; Sportartikelindustrie; Multinationales Unternehmen; Governance-Ansatz; Welt